Neuro-Oncology of CNS Tumors - Tonn, Jörg-Christian; Westphal, Manfred; Rutka, J. T.; Grossman, S.A (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Diagnosis and treatment modalities for neuro-oncologic diseases have made considerable advances in recent years. There is hardly a segment of the field of solid tumours that is experiencing such dynamic development with regard to basic scientific findings and clinical results. In the present book the world's leading experts have compiled the current practice-relevant knowledge of neuro-oncologic deseases. The book's clear structure and the uniform presentation of all chapters make this volume a valuable reference, especially for practice-oriented activities, allowing swift access to information about current treatment standards. Hence it will be of great value to both clinicians and researchers.